Validitas E-Modul Berbasis Problem Based Learning (PBL) pada Materi Fungi untuk Mengembangkan Kemampuan Berpikir Kritis - Dewi Semiati; Lilik Mawartiningsih (Biocaster : Jurnal Kajian Biologi, 2026)
The limited availability of instructional materials that support learning focused on higher-order thinking skills in the fungi curriculum for 10th-grade high school students serves as the background for this study. This situation highlights the need to develop innovative instructional materials based on Problem-Based Learning (PBL). This study aims to develop a Problem-Based Learning (PBL)-based e-module on fungi and to determine its validity as a biology instructional material. The study employed the Research and Development (R&D) method using the 4D model, implemented through the define, design, develop, and disseminate stages. However, this study was conducted only up to the develop stage, excluding the disseminate stage, as it focused on product development and validity testing. The validity test was conducted by three validators, consisting of two lecturers specializing in biology content and instructional media and one high school biology teacher, using a Likert scale assessment instrument covering the aspects of content, presentation structure, language, and media. The validation results indicate that the developed e-module achieved an average validity score of 90.1%, classified as highly valid, comprising 87.8% for content, 88.0% for presentation structure, 93.3% for language, and 91.1% for media. Based on these results, the PBL-based e-module on fungi was found to have a very high level of validity (highly valid) as a biology teaching material.